Transformation of the Prosecutor's Office: A Normative Institutional Study Towards the Attorney General and Supreme Legal Advisor (International Forum of Researchers and Lecturers, 2025)
The Prosecutor's Office of the Republic of Indonesia (Kejaksaan RI) is currently undergoing a significant paradigmatic shift following the enactment of Law No. 11 of 2021. While historically viewed primarily as a prosecution agency (Dominus Litis) in criminal matters, the current legal landscape demands a stronger role in Civil and State Administrative Law (Datun). However, the institutionalization of the Attorney General as the